2022
DOI: 10.24329/aspikom.v7i1.1067
|View full text |Cite
|
Sign up to set email alerts
|

Digital Literacy Competence Survey in Medan City

Abstract: This study measures Medan’s level of digital literacy competence. This study aims to obtain an overview of the digital literacy competencies of smartphone users in Medan City. This research was part of the National Digital Literacy Research, initiated by the Network of Digital Literacy Activists (Japelidi), conducted in 18 cities in Indonesia, involving 125 respondents from Medan City, and divided into five age segments. The research used the descriptive quantitative method. As the instrument, the research use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Previous research on women's digital competence in Indonesia (Fauzi et al, 2020;Marini et al, 2020;Sitepu & Rajagukguk, 2022;Suwana & Lily, 2017;Tisnawati et al, 2020) has identified the basic issues. First, due to their crucial role in family management, women are less involved in technology than men.…”
Section: Core Issues On Women's Digital Competence In Indonesiamentioning
confidence: 99%
“…Previous research on women's digital competence in Indonesia (Fauzi et al, 2020;Marini et al, 2020;Sitepu & Rajagukguk, 2022;Suwana & Lily, 2017;Tisnawati et al, 2020) has identified the basic issues. First, due to their crucial role in family management, women are less involved in technology than men.…”
Section: Core Issues On Women's Digital Competence In Indonesiamentioning
confidence: 99%
“…Moreover, research on immigrant youth reveals that social networking sites are being used to create transnational linkages as well as to reinvent and position their collective identities (Jung, 2006; Verkuyten et al, 2019). Namely, the development of literacy in identity‐making practices of multicultural youth is not limited to the physical social spaces of their communities but is also reinforced by transnational socialisation in virtual environments and networks (McDougall et al, 2018; McLean, 2010; Sitepu & Rajagukguk, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital literacy can be viewed as a culturally situated phenomenon; namely, a phenomenon that can be explained as dependent on and influenced by culture (McDougall et al, 2018; Sitepu & Rajagukguk, 2022). Developing digital literacy is a critical component of schooling in an increasingly multicultural society (Jung, 2006; Kimbell‐Lopez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This condition will certainly be very influential in increasing the targets and goals of campaigns on social media. However, in terms of competence, there is still a gap in the digital literacy level between the young and old generations (Sitepu & Rajagukguk, 2022). In addition, The World Giving Index in 2021 reported that Indonesia is a country with the largest Muslim majority population in the world, which reaches 236.53 million people, and the most generous country in the world These conditions should make Indonesia a fertile ground for collecting donations, including zakat.…”
Section: Introductionmentioning
confidence: 99%